Molecular Epidemiology of Rifampicin Resistance in Mycobacterium tuberculosis Using the GeneXpert MTB/RIF Assay from a Rural Setting in India. (26th October 2017) - Reddy, Raghuprakash; Alvarez-Uria, Gerardo
Abstract : The Xpert MTB/RIF assay can detect mutations in rpoB gene that confer rifampicin resistance (RR) using five overlapping probes (A, B, C, D, and E). In this study, we described our experience with the Xpert assay in a rural setting in India. During the study period, 3250 samples were processed. The result was unsuccessful in 5.7% of cases. For extrapulmonary specimens, the risk of unsuccessful result was higher in tissue biopsy and stool samples. Among samples positive for Mycobacterium tuberculosis, rifampicin resistance was indeterminate in 1.2% of them. Our results and a review of the literature showed that the most frequent mutations conferring RR were located in the region of Probe E (63.6%; 95% confidence interval [CI] 56.26–70.94), followed by Probe B (15.02%; 95% CI 11.94–18.10), Probe D (13.35%; 95% CI 10.01–16.69), Probe A (4.73%; 95% CI 1.92–7.54), and Probe C (1.61%; 95% CI 0.67–2.54). Although the high cost of the cartridges precluded using the Xpert assay for routine diagnosis of tuberculosis, our results demonstrate that the assay can be used to diagnose RR-tuberculosis in rural areas with limited laboratory infrastructure and could be a convenient tool to investigate the molecular epidemiology of RR in resource-limited settings.